2017
DOI: 10.1371/journal.pone.0181723
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin nanoparticles enhance delivery of hepatitis C virus recombinant NS2 gene

Abstract: BackgroundDevelopment of an effective non-viral vaccine against hepatitis C virus infection is of a great importance. Gelatin nanoparticles (Gel.NPs) have an attention and promising approach as a viable carrier for delivery of vaccine, gene, drug and other biomolecules in the body.Aim of workThe present study aimed to develop stable Gel.NPs conjugated with nonstructural protein 2 (NS2) gene of Hepatitis C Virus genotype 4a (HCV4a) as a safe and an efficient vaccine delivery system.Methods and resultsGel.NPs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Gelatin nanoparticles are able to deliver drugs across the blood brain barrier, which is a semipermeable barrier that is highly studied for drug delivery systems [ 55 ]. Gelatin nanoparticles have also safely and efficiently carried NS2 , a recombinant gene from the hepatitis C virus, without negatively impacting the function of the gene [ 61 ]. In addition, gelatin can be blended with other natural polymers to enhance their therapeutic behavior.…”
Section: Categories Of Protein Materialsmentioning
confidence: 99%
“…Gelatin nanoparticles are able to deliver drugs across the blood brain barrier, which is a semipermeable barrier that is highly studied for drug delivery systems [ 55 ]. Gelatin nanoparticles have also safely and efficiently carried NS2 , a recombinant gene from the hepatitis C virus, without negatively impacting the function of the gene [ 61 ]. In addition, gelatin can be blended with other natural polymers to enhance their therapeutic behavior.…”
Section: Categories Of Protein Materialsmentioning
confidence: 99%
“…In addition to the compounds (synthetic or natural) proposed as antivirals, many studies have demonstrated the potential of metallic nanoparticles, monoclonal antibodies and the CRISPR system in controlling viral infections. The antiviral activity of nanoparticles has already been demonstrated against H1N1 influenza using iron oxide [42] and against hepatitis C virus (HCV) using copper nanoparticles [43]. Monoclonal antibodies have been shown to be effective in neutralising several viruses and can mount an immune defence by acting in a way similar to that of natural antibodies [44].…”
Section: Antiviral Therapiesmentioning
confidence: 99%
“…Owing to the conversion of pure metals into nanoparticles, nanotechnology has become a powerful research technique in medical sciences and is used in the diagnosis of diseases, for carrying drugs, and even for their antimicrobial and anticancer activities [42,50,51]. These infinitesimal particles, produced using varying methods and used in different formats and compositions, are capable of transporting substances into the body, improving therapeutic efficacy and decreasing toxicity of the substance carried [43,44,52]. Nanostructured delivery systems have numerous advantages for drug delivery, including the abilities to protect the active molecules against degradation in physiological medium and to release the active substance in a controlled manner at the site of action.…”
Section: New Perspectives For the Treatment Of Viral Diseasesmentioning
confidence: 99%
“…Biodegradable nanoparticles include those based on proteins, polysaccharides, and natural or synthetic polymers. Alginate, chitosan, agarose, and gelatin are examples of natural biodegradable polymers [710]. These natural polymers have been extensively used in development of DDSs as well as scaffolds in tissue engineering.…”
Section: General Aspects Of Dds Toxicologymentioning
confidence: 99%